ASEAN-5 Economic Growth Determination 2019-2023 - Willy Kurniawan; Eni Setyowati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study analyzes the influence of Foreign Direct Investment (FDI), population growth, government spending, and unemployment rates on economic growth in five ASEAN countries-Indonesia, Malaysia, Singapore, Thailand, and Vietnam for the 2019-2023 period. The method applied is quantitative descriptive analysis with a panel data regression model through the Fixed Effect Model (FEM) approach. The findings of the study describe that FDI has a positive and significant effect on economic growth, indicating the importance of foreign investment in encouraging production and technology transfer. On the other hand, population growth and unemployment have a negative and significant effect, reflecting demographic pressures and weak labor absorption. Meanwhile, government spending had no significant effect, indicating fiscal policy inefficiencies during the COVID-19 pandemic. Overall, the study emphasizes the role of FDI as a key driver of economic growth and the need for effective human resource management in the ASEAN region.